DC-programming versus l0-superiorization for discrete tomography - Gibali, Aviv; Petra, Stefania (Analele științifice ale Universității Ovidius Constanța. Seria Matematică, 2018)
In this paper we focus on the reconstruction of sparse solutions to underdetermined systems of linear equations with variable bounds.